hCeO2@CA-074Me Nanoparticles Alleviate Inflammation and Improve Osteogenic Microenvironment by Regulating the CTSB-NLRP3 Signaling Pathway - Niu Z; Xia X; Zhang Z; Liu J; Li X (International Journal of Nanomedicine)
Zhaojun Niu,1,2 Xiaomin Xia,1,2 Zhimin Zhang,1 Jie Liu,1,2 Xue Li1,2 1Department of Stomatology, The Affiliated Hospital of Qingdao University, Qingdao University, Qingdao, People’s Republic of China; 2School of Stomatology, Qingdao University, Qingdao, People’s Republic of ChinaCorrespondence: Jie Liu; Xue Li, Email 18661801995@163.com; lixue@qdu.edu.cnBackground: It is well established that the interaction between osteogenesis and inflammation can impact bone tissue regeneration. The use of nanoparticles to treat and alleviate inflammation at the molecular level has the potential to improve the osteogenic microenvironment and serve as a therapeutic approach.Methods: We have synthesized new hollow cerium oxide nanoparticles and doped with cathepsin B inhibitor (CA-074Me) to create novel hCeO2@CA-074Me NPs. We characterized the surface morphology and physicochemical properties of hCeO2@CA-074Me NPs. Macrophage RAW 264.7 was cultured with hCeO2@CA-074Me NPs using P. gingivalis-LPS (P.g-LPS) stimulation as a model of inflammation. RT-PCR and Western blot analysis was employed to evaluate the effects of hCeO2@CA-074Me NPs on macrophage phenotype and the CTSB-NLRP3 signaling pathway. To further investigate the inflammatory osteogenic microenvironment, MC3T3-E1 cells were cultured with P.g-LPS to create an in vitro osteogenic conditions under inflammation. The cells were then co-cultured with hCeO2@CA-074Me NPs for 7, 14, and 21 d. The osteogenic ability was evaluated using ALP staining, ALP quantitative analysis, alizarin red staining, and RT-PCR analysis.Results: Findings clearly demonstrated that hCeO2@CA-074Me NPs could effectively reduce the production of ROS and inhibited CTSB-NLRP3 signal pathway, thereby significantly attenuating the damage caused by the cellular inflammatory response. hCeO2@CA-074Me NPs could also induce the polarization of macrophages towards anti-inflammatory M2 phenotype. Additionally, results confirmed that hCeO2@CA-074Me NPs could inhibit inflammation and ameliorate osteogenic microenvironment, thus promoting the osteogenesis of MC3T3-E1 cells.Conclusion: The synthetic hCeO2@CA-074Me NPs could able to modify the osteogenic microenvironment under inflammatory conditions by simultaneously inhibiting the CTSB-NLRP3 signaling pathway and regulating the macrophage phenotype through their ability to scavenge ROS. Based on these findings, our study may offer a promising approach for managing inflammatory bone damage.Keywords: cerium oxide nanoparticles, CTSB, NLRP3, inflammation, bone regeneration, osteogenic microenvironment